Case report: An unusual case of small bowel bleeding and common iliac artery pseudoaneurysm caused by an unnoticed swallowed toothpick - Xiong, Yao; Yan, Jing; Yan, Gaowu; Feng, Lei; Li, Yong; He, Suyu; Li, Ruyi; Tan, Gangcheng; Feng, Bo (Frontiers in Medicine, 2023)
Gastrointestinal (GI) bleeding is a common clinical condition that can be caused by a variety of reasons. Bleeding can occur anywhere in the GI tract, and it usually presents as vomiting of blood, melena or black stools. We herein present a case of a 48-year-old man who was ultimately diagnosed with perforation of the lower ileum, pseudoaneurysm of the right common iliac artery, lower ileum-right common iliac artery fistula, and pelvic abscess caused by accidental ingestion of a toothpick. This case suggests that accidental ingestion of a toothpick may also be the cause of GI bleeding in some patients. For patients with unexplained GI bleeding, especially those with small bowel bleeding, a rational and combined use of gastroduodenoscopy, colonoscopy, unenhanced and contrast-enhanced abdominal CT can help detect the causes of GI bleeding and improve diagnostic accuracy.